Role of exosomes in gastrointestinal physiology and pathophysiology - Wellington, Vivian Naa Amua; Singh, Soudamani (Frontiers in Immunology, 2026)
Exosomes, which are molecular cargo-containing, nanosized extracellular vesicles formed through double invagination of the plasma membrane, have emerged as important mediators of intercellular communication within the gastrointestinal tract. In addition to its established function in digestion and nutrient uptake, the gastrointestinal tract is central to immune regulation and maintenance of epithelial barrier integrity. Exosomes derived from intestinal epithelial cells, the gut microbiota and gut resident immune cells are key in sustaining intestinal homeostasis and regulating host-microbiota interactions. Dysregulation of these vesicles is increasingly linked to gastrointestinal disease pathogenesis, including inflammatory bowel disease. Currently, exosomes are being explored for use as diagnostic biomarkers and therapeutic agents in gastrointestinal ailments. In this review, we examine the roles of exosomes in gastrointestinal health and disease, highlighting their contributions in the regulation of epithelial barrier function, modulation of immune responses and communication with the gut microbiota. We further discuss the dysregulation of exosome-mediated signaling pathways in IBD and assess their potential as next-generation therapies for gastrointestinal disorders.